PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN ORANG TUA DALAM MENYEKOLAHKAN ANAKNYA DI TK MUJAHIDIN 2 PONTIANAK KECAMATAN PONTIANAK TIMUR - Siti Rahmawati Sa’baniah; Dedi Hariyanto; Neni Triana Maswardi (Jurnal Produktivitas: Jurnal Fakultas Ekonomi Universitas Muhammadiyah Pontianak, 2018)
The purpose of this study is to determine the effect of marketing mix on the decision of parents to send their children to the Institute of Kindergarten Mujahidin 2 Pontianak East Pontianak district. The method used in this research is descriptive. Sampling technique using saturated sampling method, the sample used amounted to 95 respondents.The result of research based on simple linear regression analysis with regression equation Ŷ = 1,604+0,642X stated that every increase of one-unit value from marketing mix variable, then value of purchasing decision increase 0,642. The results of research based on the correlation coefficient (R) of 0,547 means there is a strong relationship between the marketing mix with the purchase decision. While the results of research based on the coefficient of determination (R2) of 0.229 means the influence of marketing mix of purchasing decisions amounted to 22,9% and the remaining 771% influenced by other factors not examined in this study. While the feasibility test model (Test F) states that a simple linear regression model can be used to predict purchasing decisions that are influenced by the marketing mix with a value of F arithmetic 39,735 greater than the value of F table 3.94 or 39,735 > 3.94. Thus, it can be concluded that marketing mix variables have a significant effect on purchasing decisions